Impacts and implications of oil palm in Uganda’s Lake Victoria Islands - The case of Kalangala district - Kiyingi, G.K.; Opige, M.; Ssemmanda, R.; Kisakye, J.; Wamala, P. (2020)
This synthesis paper brings together numerous studies on the impacts of oil palm plantations established in Kalangala district since 2002. It highlights the lessons, and presents recommen¬dations for reviewing the Kalangala oil palm model in the light of the evidence presented.